MENGAKSES ASPEK AFEKTIF DAN KOGNITIF PADA PEMBELAJARAN OPTIKA DENGAN PENDEKATAN DEMONSTRASI INTERAKTIF - Riskan Qadar (Universitas Sriwijaya, 2015)
This study aims to assess the affective and cognitive aspects of learning optics with an interactive demonstration approach . Research using experimental design and involving as many as 33 candidates for the fifth semester of physics teacher in East Kalimantan LPTK as research subjects . Quantitative data was collected using observation sheet for affective aspects and models of multiple-choice test instruments for the cognitive aspects . The results showed that the affective assessment showed their role to improve learning . Prospective teachers show things that are associated with such emotional feelings, values ​​, appreciation , antuisme , and motivation in classes to improve cognitive abilities . Phase affective aspects have shown that the percentage of appropriate behavior comprises the step of receiving , responding to , respect, organization , and characterization . The cognitive abilities of future teachers has increased by 0.48 N -gain .